Microbiological analysis of fresh produce sold at Florida farmers' markets. (October 2018) - Roth, Lisa; Simonne, Amarat; House, Lisa; Ahn, Soohyoun
Abstract: The number of farmers' markets in the U.S. has increased with the consumer demand for locally grown fresh produce. The popularity of farmer' markets, however, also raises concern for safety of food sold at these markets. The objective of this study was to analyze the microbial quality of fresh produce from farmers' markets and compare it with the quality of produce from traditional retail markets. Between July 2016 and April 2017, 401 fresh produce samples, including 301 samples from farmers' markers and 100 from supermarkets, were collected from 9 farmers' markets and 12 supermarkets in North and Central Florida. Four commodities (tomatoes, leafy greens, berries and spinach) were purchased and analyzed for counts of total coliforms and generic Escherichia coli as well as the presence of foodborne pathogens including Salmonella, Listeria monocytogenes, and E. coli O157:H7, using 3M E. coli /Coliform Count plates and real-time PCR, respectively. Total coliform prevalence was 50.8% (153 of 301) and 34% (34 of 100) in farmers' market and supermarket produce, respectively. Total coliform counts of farmers' market leafy greens (2.3 log CFU/g) and spinach (2.4 log CFU/g) were significantly higher ( P  < 0.05) than their supermarket counterparts (1.1 log CFU/g and 0.70 log CFU/g, respectively). Generic E. coli was detected in 2.3% (7 of 301) of farmers' market produce, and none in supermarket samples. Of farmers' market-collected samples, generic E. coli was detected in 5.8% of spinach, 2.6% of leafy greens and 2.2% of tomatoes, and, on average, was detected at low levels (<1 log CFU/g). L. monocytogenes was detected in 3.9% (2 of 52) and 2.6% (2 of 77) of farmers' market spinach and leafy greens, respectively. No supermarket samples were positive for L. monocytogenes . One farmers' market tomato and one supermarket berry sample were positive for Salmonella . No E. coli O157:H7 was detected in this study. The occurrence of L. monocytogenes and higher prevalence of coliform indicates the need for improved monitoring of fresh produce from farmers' markets and public education for the importance of washing produce before consumption. Highlights: Higher total coliform prevalence in farmers' market produce. Low level of generic E. coli found in 2.3% of farmers' market produce samples. L. monocytogenes detected in 3.9% of farmers' market spinach. Improved monitoring of farmers market fresh produce is needed.